Educação Ambiental e Gerenciamento Integrado de Resíduos Sólidos: Influência do Grupo de Apoiadores no Modelo de Gestão de Uma Cooperativa de Reciclagem de Resíduos Sólidos | Environmental Education and the Integrated Management of Solid Waste: The Influe (PEGADA - A Revista da Geografia do Trabalho, 2014)
Introduction: This research derives from our experience of support groups since 2006. In seeking to understand the way in which a co-operative organization works, it is necessary to find out how and by whom it is managed. In order to put this organization into context, this project needed to establish a perspective that addressed the relevant points: society, exclusion, garbage, job insecurity. The research aims to show how support groups in a social intervention project develop a dual role for beneficiaries: 1) as institutional agents who use their respective institutions to direct decisions and actions to make changes in the work place of the beneficiary, 2) to influence the liberation of geographic space in the work of beneficiaries (cultural, educational, ideological, social and psychological). The hypothesis is that those who bring this about are the support groups because the original co-operative perspective sprang from them, and all management processes for more than ten years have taken place through this group. Our thesis seeks to find the evidence and investigate whether there is a real problem. It will be carried out through a systematic analysis of management over the last ten years. Methodology and development: An in-depth analysis will require not only a review of the literature concerning different studies of Cooperlix in Presidente Prudente, SP, but mainly the institutional articulation mechanisms which characterize the geography of the work, with the aim that the study will lead us to a socio-organizational structure that goes beyond the co-operative and its members. Once all the research involving the collection of data from various sources has been completed, we will make use of a research practice involving intensive direct observation (observation and interview), and also extensive direct observation (questionnaire). The research will be exploratory, aiming to identify and systematize current information concerning the scope of work and its influence on the behavior of those involved. Documentary research will be carried out within the different organizations involved with the intention of mapping influence and interaction between them and Cooperlix. Individuals who make up the support groups, selected according to certain criteria, will be interviewed. Interviews will be conducted with the co-operative in order to identify and interpret their perceptions of the changes it has undergone, influenced by the support groups. It will be possible to identify the management model adopted in the last ten years from this information. Analysis will take place at different times as each stage of the research will require individual analysis. Final thoughts: The results of this research will contribute to establishing an understanding of the actions and practices of the support groups.